Terrace Heroes - Kelly, Graham (Sport in the Global Society, 2005)
The 1930s saw the birth of the football idol - prototype for today's powerful media sport stars. The players of the 1930s were the first generation of professionals, yet until recently the life and careers of footballers of this generation has been little studied. In 1930s Britain, football became increasingly commercialized, and the rise and development of both local and national media enabled players to become widely recognized outside of their immediate local context for the first time. Tracing the origins, playing careers and 'afterlives' of several First Division players of the era, Graham Kelly's revealing history explores the reality of living in Britain between the wars and draws interesting comparisons with lives of the modern football hero today.